The influence of summary writing on the development of reading skills in a foreign language. (July 2016) - Marzec-Stawiarska, Małgorzata
Abstract: The study investigates the influence of summary writing in an FL on the development of students' EFL reading skills. Eighty university students participated in a six-month long quasi-experimental study. They were divided into an experimental and a control group, both of which followed the same syllabus and read the same texts. The difference between them was that the experimental group regularly wrote summaries of the texts they had read while the control group engaged in typical FCE reading tasks: multiple choice questions, true/false statements and matching. The development of students' reading skills was measured by assessing their level of comprehension before and after an EFL course involving summary writing. The study showed a statistically significant difference in the reading skills of the two groups suggesting that summarising has a positive influence on reading development. Progress in students' reading skills did not correlate with the quality of the summaries they wrote. Summary writing was shown to be highly beneficial for weaker readers. The results of the study might assist in the search for effective techniques for developing text comprehension in the FL classroom.